MANAJEMEN SARANA DAN PRASARANA LABORATORIUM KIMIA DI SMA NEGERI 2 BENGKULU SELATAN - Sri Yuliarti; Rohiat Rohiat; Osa Juarsa (Manajer Pendididikan, 2017)
The objective of the study is to know about the management of chemist laboratory of SMA N2 South Bengkulu. The method of the study is descriptive qualitative. The objects are chemist teacher and the user of laboratory SMA N2 South Bengkulu. The techniques of the data are interview, observation and documentation study.  The conclusion shows that: 1. the planning of the equipments of chemistry laboratory during this time do by arranges the draft what they need every year, 2. The amounts of the equipments is limited 3. The using of chemistry laboratory runs well. 4. The inventories of chemistry laboratory are procedurally. 5. The protection of chemistry laboratory is low because they do not have laborer. 6. The cleaning out of the equipments of the laboratory is not procedurally because the user has no knowledge about it.